High resolution microscope of the future: using an ultrashort wavelength laser to image integrated circuits - Tippie, Abbie, author; Kautz, Christopher, author; Eifealdt, Eric L., author; Menoni, Carmen S., author (Colorado State University. Libraries, 2006)
As the dimensions of integrated circuits continue to decrease, new metrology tools that acan inspect the nanoscale patterns and features need to be developed. In this project we developed a compact zone plate imaging tool using a 46.9 nm laser as its illumination source. The microscope can render images in transmission and reflection mode with unsurpassed spatial resolution. In addition it is very versatile as it incorporates a visible imaging system that allows the user to pre-select the area if interest to image at higher magnification with the 46.9 nm light. Image acquisition is automated through control software developed for the system. This is the highest resolution table-top microscope at this wavelength ever reported.
Keywords: Integrated circuits; Microscopes